Exploring Gender Disparities in Scholarly Communication Metrics within Digital Library Research - Mohammad Nazim; Ali, Altaf; Gupta, Amrataksh; Mushahid Ali (DESIDOC journal of library & information technology, 2025)
This study investigates gender disparities in scholarly communication in digital library research over 30 years from 1993-2022, focusing on authorship roles, citation metrics, external funding, and open-access publishing. A bibliometric approach was adopted, analysing 831 publications extracted from the Core Collection database of Web of Science. The gender of the first, last, and sole authors was identified using the Gender API and supplementary online searches. Statistical tests, including the Wilcoxon Signed-Ranks test, Independent Samples t-test, and Chi-Square test, were employed to examine gender differences in citation metrics, access to research funding, and open-access publishing across different authorship positions. The findings reveal persistent gender disparities, with male authors dominating senior authorship positions and high-impact publications. However, female first authors demonstrated competitive citation metrics and a slight advantage in open-access publishing. Geographical analysis showed varying levels of gender parity across countries, with the USA, Spain, and England exhibiting a balanced gender distribution, where female authors’ contributions are nearly equal to those of male authors. Despite progress toward gender equity, challenges remain in access to funding and leadership roles. The findings highlight the need for institutional policies that promote equitable access to research funding and address the barriers that hinder women from securing financial support for their research endeavors.